Characterisation, Classification and Suitability for Oil Palm of Some Common Soils in Tawau-Semporna Area, Sabah - Sugandi, Arif (2005)
Seven most common soils on different parent materials from oil palm estates in Tawau-Semporna area, Sabah were selected for this study. The study was carried out due to the lack of detailed information for proper classification and management of the soils. The objectives are therefore to determine their physical, chemical, mineralogical and micromorphological properties; to classify them according to the FAORJNESCO Legend, the Sabah Classification System, the World Reference Base (WRB) and the Soil Taxonomy and to compare the usefulness of these different systems; and to evaluate their fertility status and suitability for oil palm. All the soils have deep solum (>I00 cm) and oxic or argillic horizons. Soil color and texture vary depending on the parent materials. Bulk density of andesitic soils is lower than the rest of the soils. Soil pH of the soils are acidic (4.0) and have a net negative charge. Except for the andesitic basalt soil. the studied soils have mainly low amount of bases and capacity exchange cation (CEC). Soil N. P and K are also mostly lo~vS. oil Mg is high on the andesitic basalt and tuffaceous sedimentary rocks soils. For oil palm cultivation. the soils are of low to very low fertility. Most of the studied soils are highly weathered due to the dominance of kaolinite, quartz. goethite. hematite and gibbsite. Andesitic basalt and tuffaceous sedimentary rock soils are however less weathered as indicated by the presence of 2:l clay minerals, illite and feldspars. The most interesting mineralogical and micromorphological anomaly is the presence of cristobalite in the soils over sedimentary rocks indicating the volcanic influence on the soils through the addition of volcanic ash and by the presence of tuffaceous materials. The studied soils are classified into different soil types according to the various classification systems indicating each soil have specific properties. The classification of soils according to the WRB systems appears to give more detailed information and better interpretation on soil properties and management than the FAOIUNESCO legend and Soil Taxonomy. Based on the Fertility Capability Classification, the studied soils are classified into different fertility groups with major problems of low CEC, A1 toxicity and K deficiency. No major constraint is encountered on the andesitic basalt soil due to its